Paperitähti - Kaurismäki, Mika; Salminen, Timo; Hämäläinen, Pirkko; Lauri, Hannu; Soisalo, Minna (Future Film, 2007)
A model finds herself in gaol after killing an alcoholic lover in self-defence. Beaten up by her photographic lover, she can't find jobs, and reminisces about her teenage years. [www.bfi.org.uk]
Keywords: DVD-Video